Engaging contested minoritized commemorations: A métissage inspired inquiry into a vandalized bilingual (French-English) stop sign - Scott, David; Gani, Raphaël; Gobran, Jessica (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
This article examines a case of what we term a contested minoritized commemoration involving the vandalization of multiple bilingual (French-English) stop signs in the Mission District of Calgary (Alberta). We argue that these bilingual stop signs are minoritized commemorations and the vandalization of the French portion of these signs reflects a form of contestation. Drawing on hermeneutic and métissage methodologies, we weave together autobiographical texts stemming from how we individually related to and made sense of this act of anti-Francophone vandalism. Through interpreting our textual braids in relation to one another, we show how such an approach offers relational possibilities for engaging the educational challenges accompanying contested minoritized commemorations.